Implementation of Public Service Innovation Through the OK3S System (One Click Three Services) In the Muhammadiyah Sukabumi University Library - Robi, Alfa; Saleh, Munandi; Hegia Sampurna, Rizki (PT. Multidisciplinary Press Indonesia, 2025)
This research aims to find out how to implement public service innovation through the OK3S (One Click Three Services) system at the Muhammadiyah University Sukabumi Library. This study used a descriptive qualitative method. Data collection techniques using interviews, observation and document analysis. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. Research location at the Muhammadiyah University Sukabumi Library. The research results show (1) the Use dimension, the OK3S (One Click Three Services) system has provided convenience for users, namely final year students, (2) Performance, there has been an increase in the performance of Muhammadiyah University Sukabumi library employees, (3) User attitudes and beliefs, Implementation of the OK3S system innovation has a positive impact on feedback from stakeholders, especially final year students, lecturers and related stakeholders, (4) Integration into the organization (Integration into the organization) , the OK3S system is integrated with SIAK (Academic and Financial Information System) so that students only need to use the email as recorded in SIAK to access OK3S, (5) Effectiveness of implementation effort (Effectiveness of implementation efforts) in its implementation has passed the preparation, system development, and implementation of the system. However, in practice, implementation is not optimal due to several obstacles encountered.